Analisis Kesiapan Mahasiswa Calon Guru Terhadap Kebijakan MBG di Sekolah: Tinjauan Teori Implementasi George C. Edwards III - Sri Yunita Simanjuntak (Majalah Ilmiah METHODA, 2026)
The Free Nutritious Meal (MBG) policy in schools represents a strategic government move to enhance human capital quality and combat stunting. However, the success of its implementation hinges significantly on the readiness of stakeholders, including pre-service teachers who will eventually serve as implementers in schools. This study aims to analyze the readiness of pre-service teachers regarding the MBG policy using George C. Edwards III’s policy implementation theory, which encompasses four key indicators: communication, resources, disposition, and bureaucratic structure. A descriptive qualitative method was employed, utilizing open-ended surveys distributed to fourth-semester students in the Office Administration Education study program. The findings indicate that communication regarding policy dissemination remains limited, while regarding resources, students perceive a need for specialized training in program logistics management. Student disposition reflects a positive and supportive attitude, though there are concerns regarding the burden of ancillary administrative tasks. Regarding bureaucratic structure, clear task allocation (Standard Operating Procedures) is essential to avoid distorting the teacher's primary role of instruction. Overall, pre-service teachers demonstrate good mental readiness but require strengthened managerial competencies before being deployed to schools